Treatment of lead-contaminated water using activated carbon adsorbent from locally available papaya peel biowaste. (1st April 2016) - Abbaszadeh, Sahar; Wan Alwi, Sharifah Rafidah; Webb, Colin; Ghasemi, Nahid; Muhamad, Ida Idayu
Abstract: The performance of activated carbon (AC) produced from papaya peel (PP) as a locally available bioderived adsorbent in the removal of Pb(II) from metal-contaminated water is reported. Utilization of natural biowastes, such as papaya peel, in this way could assist with waste minimization at the same time as providing a new source of activated carbon for wastewater treatment. Lead pollution in water bodies is critical in countries such as Malaysia, yet removal via this locally sourced waste material has not been considered before. Using papaya peel activated carbon (PP–AC) in batch mode, the effects of initial pH (3–7), adsorbent dosage (10–200 mg), initial Pb(II) concentration (10–200 mg/L), contact time (10–180 min) and temperature (25, 35 and 50 °C) were studied separately. The best result was obtained at pH 5, with an adsorbent dosage of 100 mg, Pb(II) ion concentration of 200 mg/L and a contact time of 2 h, with over 93% of the Pb(II) being adsorbed. It was observed that the time required to reach equilibrium decreased with increasing initial concentration of Pb(II) in the solution. The experimental data were consistent with both Langmuir and Freundlich adsorption models. The data also fitted very well ( R 2 = 0.99) to a pseudo-second-order kinetic model, suggesting that the bioadsorption is a chemisorption process. In addition, thermodynamic parameters such as Δ G °, Δ H ° and Δ S ° were calculated. The adsorption of Pb(II) on PP–AC was found to be spontaneous and exothermic under standard conditions. Desorption studies confirmed the applicability of hydrochloric acid (HCl) as a desorbing agent with great efficiency (>97%) and a regeneration of approximately 96%. Overall, the efficiency of the Pb(II) uptake process using PP–AC was more than 40% higher than values reported for most crop-based adsorbents, confirming its potential for use in wastewater treatment processes. Highlights: Activated carbon papaya peel (PP–AC) has high Pb(II) adsorption capacity (38.31 mg/g). Optimum pH, adsorbent dosage, agitating time, initial concentration and contact time are presented. Best equilibrium isotherms and kinetic models are evaluated. The Pb (II) biosorption from PP–AC is feasible, spontaneous with exothermic nature.